2016
DOI: 10.1111/jocn.13077
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Spanish women undergoing hysterosalpingography as part of the infertility process: a phenomenological study

Abstract: Knowing the experiences of these women could help nurses, midwives and physicians to provide better patient-centred care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…Why it should claim to be ‘hermeneutic phenomenology’ (p. 804) is thus somewhat obscure. A similar situation is found in another study (Fernández‐Sola, Martınez‐Caba, Hernandez‐Padilla, Carmona‐Samper, & Granero‐Molina, ) making claims initially to be a ‘phenomenological qualitative study’ (p. 494) and later to be a ‘qualitative study based on Gadamer's hermeneutic phenomenology’ (p. 495). With the aim of the study being to reach an understanding of their participants’ experiences rather than simply describing the experience itself, their focus on time and culture and their adherence to the method, it is clearly a hermeneutic study and nothing else.…”
Section: Discussionsupporting
confidence: 73%
“…Why it should claim to be ‘hermeneutic phenomenology’ (p. 804) is thus somewhat obscure. A similar situation is found in another study (Fernández‐Sola, Martınez‐Caba, Hernandez‐Padilla, Carmona‐Samper, & Granero‐Molina, ) making claims initially to be a ‘phenomenological qualitative study’ (p. 494) and later to be a ‘qualitative study based on Gadamer's hermeneutic phenomenology’ (p. 495). With the aim of the study being to reach an understanding of their participants’ experiences rather than simply describing the experience itself, their focus on time and culture and their adherence to the method, it is clearly a hermeneutic study and nothing else.…”
Section: Discussionsupporting
confidence: 73%
“…Anxiety "I wish the process wasn't so long, there was a lot of anxiety over the months and it gets really long." (Fernández-Sola et al, 2016) 15 Attachment "Neither of us wants to be tied up with a kid and lose the freedom to relax and travel as we normally do regularly. It is less hassle without children."…”
Section: Number Of Studiesmentioning
confidence: 99%
“…Those corroborated existing evidence that addressed comfort and discomfort (Schoener & Krysa, 1996) and coping strategies (Ismail & Moussa, 2017) in infertile patients. Also, the emergence of dignity in this health context is an interesting aspect as it may claim the delivery of a respectful approach in fertility care (Arya & Dibb, 2016;Batool & de Visser, 2015;Bell, 2012;Benasutti, 2003;Cipolletta & Faccio, 2013;Ferland & Caron, 2013;Fernández-Sola, Martínez-Caba, Hernández-Padilla, Carmona-Samper, & Granero-Molina, 2016;Mahon & Cotter, 2014;Olafsdottir, Wikland, & Möller, 2013). The absence of a patient-centered care has been previously highlighted as the origin of patients' burden and eventual dropouts from ART (Boivin et al, 2012;Huppelschoten et al, 2013).…”
Section: Table 4 Number Of Nanda-i Nursing Diagnoses Per Studies (N)mentioning
confidence: 99%
“…However, a search of the literature found no studies evaluating the effects of education and counselling on reducing both pain and anxiety in women undergoing HSG. Some studies suggested that nurses should conduct studies on infertile couples undergoing infertility treatment on the subject (Fernández‐Sola, Martínez‐Caba, Hernández‐Padilla, Carmona‐Samper, & Granero‐Molina, ; Wilson & Leese, ). Nurses also should assess and prevent anxiety and pain and enhance the comfort of the patients, and psychologically prepare patients before and during the HSG procedures.…”
Section: Introductionmentioning
confidence: 99%